Agreement on surroggy maternity as a regulator of these legal relations - Hnativ, Oksana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
Thanks to the high level of development of modern medicine, citizens of Ukraine who are faced with the problem of infertility have the opportunity to resort to the help of auxiliary reproductive technologies. In the presence of medical indications, citizens can apply for the services of a surrogate mother. The article considers one of the most interesting methods of assisted reproductive technologies from a legal point of view - surrogate motherhood. Despite the fact that legal grounds for surrogate motherhood appeared in Ukraine back in 2011-2013 (when the relevant normative acts were adopted and entered into force), now there are many practical and theoretical problems related to the institution of surrogate motherhood. At the moment, Ukraine has not adopted a single normative legal act regarding the use of assisted reproductive technologies, however, the current legislation contains a sufficient number of norms regulating this issue. It is worth noting that in Ukraine, a contract of surrogacy can be both commercial and free of charge. The problem of its legal nature is also complicated by the fact that the legislator still did not define the concept of contract, did not foresee the form of conclusion of the contract and its essential conditions. The author points to the presence of visible «gaps» in the current legislation. At the end of the article, the author came to the conclusion about the possibility of eliminating conflicts between the current legislation and the existing judicial practice by adopting a single normative act. The article summarizes national and foreign judicial practice on this issue, and formulates the author’s position. It is very important to talk about the need for availability of information regarding the use of assisted reproductive technologies. Therefore, it is important to systematize and organize such information, creating a single regulatory act that regulates the application of such a method of assisted reproductive technologies as surrogacy, as well as to provide a place for a contract on surrogacy.